Duodenal cytochrome b (Cybrd1) ferric reductase functional studies in cells. Issue 10 (22nd September 2017) - Schlottmann, F.; Vera-Aviles, M.; Latunde-Dada, G. O.
Abstract : A single nucleotide polymorphism (rs10455) in the last exon of the Dcytb gene in C282Y hemochromatosis subjects exhibited increased ferric reductase activity in transgenic CHO cells. Abstract : Dietary non-heme ferric iron is reduced by the ferric reductase enzyme, duodenal cytochrome b (Dcytb), before absorption by the divalent metal transporter 1 (DMT1). A single nucleotide polymorphism (SNP rs10455 mutant) that is located in the last exon of the Dcytb gene was reported in C282Y haemochromatosis HFE subjects. The present work therefore investigated the phenotype of this mutant Dcytb in Chinese hamster ovary (CHO) cells. These cultured cells were transfected with either wild type (WT) or the SNP vector plasmids of Dcytb. Ferric reductase assays were performed in Dcytb transgenic CHO cells using the ferrozine spectrophometric assay protocol. The Dcytb SNP rs10455 showed a gain-of-function capability since ferric reductase activity increased significantly ( p < 0.01) in the transgenic cells. Varying ferric reductase activity was found when CHO cells were pretreated with modulators of Dcytb protein expression. Although ferric reductase in endogenous CHO cells increased with deferoxamine or CoCl2, iron loading with ferric ammonium citrate (FAC) had the opposite effect. Taken together, the study reveals a gain-of-function phenotype for Dcytb rs10455 mutation that could be a putative modifier of colorectal cancer risk, with attendant variability in penetrance among human HFE C282Y homozygotes.